TEACHING STUDENTS HOW TO MAKE INDIVIDUAL HORSES IN NATIVE LANGUAGE AND LITERACY CLASSES USING INTERACTIVE TECHNIQUES - Bolibekov Alisher Abdusalomovich; Karimova Go'zal Abdurashidovna (American Journals, 2023)
Teaching students to be able from their native language is very important in today's world because it forms the basis of their communication skills. It is also very important to form literary skills in students. Using interactive methods can help make learning more fun and effective. In this article, we will learn how to use interactive methods when teaching students in their native language and literacy classes, in particular when making paper horses.